2022
DOI: 10.1186/s12877-022-03092-6
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive quality of elderly rehabilitation nursing staff in medical and health care institutions in Liaoning Province, China: a cross-sectional study

Abstract: Background With the global aging problem is becoming increasingly severe, the elderly care has become an important issue that needs attention. Chinese government attaches great importance to the development of medical and health care institutions, and is committed to improving the comprehensive quality of elderly rehabilitation nursing staff in medical and health care institutions. Methods From June to September 2019, a cross-sectional study among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Therefore, there is a need to individually set up spiritual support according to the elderly’s characteristics to expand their relationships and improve emotional support. However, there is an overall low quality of nursing staff, a lack of personnel, and an unbalanced ratio of older people and nursing staff in Chinese elderly care institutions [ 22 ], which leads to an urgent need for middle-aged and older people to improve the service quality of elderly care institutions, but a relatively low pursuit of a very high level of service quality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, there is a need to individually set up spiritual support according to the elderly’s characteristics to expand their relationships and improve emotional support. However, there is an overall low quality of nursing staff, a lack of personnel, and an unbalanced ratio of older people and nursing staff in Chinese elderly care institutions [ 22 ], which leads to an urgent need for middle-aged and older people to improve the service quality of elderly care institutions, but a relatively low pursuit of a very high level of service quality.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, most elderly care institutions only provide general life care or are only equipped with simple medical facilities, which cannot meet the medical care requirements of the elderly [ 20 21 ]. In terms of service quality, there is a lack of professional nursing personnel and a severe imbalance in the ratio of nursing personnel to the elderly [ 22 23 ]. Related studies also found that the quality of nursing personnel in some elderly care institutions is generally low, and the service attitudes need to be improved [ 24 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…The shortage of healthcare personnel and the imperfect talent training system in China pose a serious challenge to the integrated medical and nursing institutions [25], an issue that was also raised by the operational managers of the institutions participating in this study. According to some participants, this limits the highly e cient development of medical and nursing integration to a certain extent, making it resistant to e cacious improvement in the level of services.…”
Section: Discussionmentioning
confidence: 99%
“…The rapid development of integrated medical and eldercare institutions is a response to this demographic shift. These institutions, as their designation suggests, are equipped with both medical and caregiving capabilities, offering a range of services including psychological comfort, daily life care, palliative care, and medical assistance to the older adult ( 4 ). They mitigate to some extent the societal pressures brought about by population aging.…”
Section: Introductionmentioning
confidence: 99%